TNM atlas illustrated guide to the TNM classification of malignant tumours - Brierley, James 1956-; Asamura, Hisao; Van Eycken, Elisabeth; Rous, Brian Arthur (Wiley-Blackwell, 2020)
"Introductory Notes The following sites are included: Lip, oral cavity, Pharynx: oropharynx, nasopharynx, hypopharynx, Larynx: supraglottis, glottis, subglottis, Nasal cavity and paranasal sinuses, Malignant melanoma of upper aerodigestive tract, Major salivary glands, Thyroid gland. Carcinomas arising in the minor salivary glands of the upper aerodigestive tract are classified according to the rules for tumours of their anatomic site of origin, e.g., oral cavity"--
Keywords: Neoplasms / classification; Atlas; Bildband